2020
DOI: 10.33448/rsd-v9i12.11391
|View full text |Cite
|
Sign up to set email alerts
|

Secagem de tijolos cerâmicos industriais e estimativa de parâmetros do processo: uma abordagem concentrada avançada

Abstract: Este trabalho objetiva estudar a secagem de sólidos porosos e com forma arbitraria usando o método da análise concentrada. Um modelo matemático fenomenológico avançado baseado numa análise concentrada e sua solução exata são apresentados para predizer as transferências de massa e calor em tijolos cerâmicos vazados industriais e estimar os coeficientes de transporte. Diferentes simulações foram realizadas para avaliar o efeito da temperatura do ar no processo de secagem. Resultados transientes do teor de umidad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In the consulted literature, no studies were found that evaluated the drying process of ceramic materials at low temperatures (less than 50 • C). In addition, such works are limited to simpler geometries, such as hollow bricks and ceramic blocks [1,3,5,7,8,13,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It was also noticed that the only operational parameter evaluated in the drying process of ceramic materials reported in the literature is the temperature of the drying air; parameters not being evaluated, for example, were cases involving the same temperature and different values for relative humidity and/or velocity, including dimensions variations.…”
Section: Introductionmentioning
confidence: 99%
“…In the consulted literature, no studies were found that evaluated the drying process of ceramic materials at low temperatures (less than 50 • C). In addition, such works are limited to simpler geometries, such as hollow bricks and ceramic blocks [1,3,5,7,8,13,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It was also noticed that the only operational parameter evaluated in the drying process of ceramic materials reported in the literature is the temperature of the drying air; parameters not being evaluated, for example, were cases involving the same temperature and different values for relative humidity and/or velocity, including dimensions variations.…”
Section: Introductionmentioning
confidence: 99%